Preparation, Synthesis and Characterization of La(1-x)Sr(x)MnO3 Alloy - Ramlan Ramlan; Fatma Husaini; Jan Setiawan; Ferry Budhi Susetyo; Hamdan Akbar Notonegoro; Silviana Simbolon; Dwi Nanto; Yunasfi Yunasfi (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Magnetic particles have been used for hyperthermia by inserting ferromagnetic material into tumor tissue. La(1-x)Sr(x)MnO3 is one of the best candidates for hyperthermia due to higher magnetic at ambient temperature and their Curie temperature easily adjusted. This research synthesized La(1-x)Sr(x)MnO3 using the ball milling technique. Several heat treatments were also conducted after ball milling processing. Various investigations, including SEM-EDS, XRD, DSC, and VSM, were conducted. LaMnO3 has a hexagonal structure, which has the space group R -3 c. From the diffraction pattern seen in LaMnO3 and La0.9Sr0.1MnO3 seen at angles 32.376 and 32.706, it looks separate like the database diffraction pattern. In La0.9Sr0.1MnO3, these two peaks are seen to be increasingly separated. In contrast to the diffraction patterns of La0.7Sr0.3MnO3 and La0.5Sr0.5MnO3 at an angle of 32.376, there is a decrease in intensity. The specific heat capacity of the alloy with Sr substitution of 0.3 has a greater value than that without substitution and the lowest occurs in the alloy with Sr substitution of 0.1. The magnetization value for Sr substitution is 0.3 higher than for other alloys.